2023
DOI: 10.1002/jac5.1855
|View full text |Cite
|
Sign up to set email alerts
|

Defining pharmacist activities in ambulatory heart failure clinics: North American survey and modified Delphi study

Abstract: BackgroundPharmacists are key members of multidisciplinary heart failure (HF) clinics; however, there is variation in their roles and activities. This study aimed to: (1) define current roles of HF clinic pharmacists and (2) develop a consensus‐based list of key activities for HF clinic pharmacists.MethodsIn part 1, we invited Canadian and American HF clinic pharmacists to complete a survey on activities currently performed in the HF clinic. Part 2 consisted of a three‐round modified Delphi study including onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…Early observational studies of pharmacist‐led HFrEF medication titration approaches have found an increase in GDMT therapy uptake and associated improvements in patient outcomes 8 . In North America, pharmacists have an increasing presence in HF medication management, although their specific roles and delegated activities vary 18 . However, consensus among pharmacists specializing in HF care has recently emerged such that their role should focus on “hands‐on” pharmacotherapy assessment and management including medication initiation and titration, modification of pharmacotherapy for comorbid conditions (e.g., atrial fibrillation and diabetes), and medication adjustment based on adverse drug events 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early observational studies of pharmacist‐led HFrEF medication titration approaches have found an increase in GDMT therapy uptake and associated improvements in patient outcomes 8 . In North America, pharmacists have an increasing presence in HF medication management, although their specific roles and delegated activities vary 18 . However, consensus among pharmacists specializing in HF care has recently emerged such that their role should focus on “hands‐on” pharmacotherapy assessment and management including medication initiation and titration, modification of pharmacotherapy for comorbid conditions (e.g., atrial fibrillation and diabetes), and medication adjustment based on adverse drug events 18 .…”
Section: Discussionmentioning
confidence: 99%
“…In North America, pharmacists have an increasing presence in HF medication management, although their specific roles and delegated activities vary 18 . However, consensus among pharmacists specializing in HF care has recently emerged such that their role should focus on “hands‐on” pharmacotherapy assessment and management including medication initiation and titration, modification of pharmacotherapy for comorbid conditions (e.g., atrial fibrillation and diabetes), and medication adjustment based on adverse drug events 18 . In the present study, we show that pharmacists who are empowered by their team and institution to do this work can successfully implement such medication management activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation